Prevalence of pulp stones in cone beam computed tomography - Rodrigues, Vanessa; Scamardi, Isabella; Schacht Junior, Cezar Fioravanti; Bortolotto, Milena; Manhães Junior, Luiz Roberto [UNESP]; Tomazinho, Luiz Fernando; Boschini, Sheila (Dental Press International, 2014)
Introduction: Calcifications of the pulp chamber, known as pulp stones, are common and may be adhered or not to dentin. These changes are detected during routine radiographic evaluations as single or multiple circular or ovoid radiopaque images measuring more than 200 μm. Used in Endodontics, cone-beam computed tomography (CBCT) may demonstrate root and coronary anatomy and detect calcifications, which may help to make an accurate diagnosis. Objective: This study assessed the prevalence of pulp stone on CBCT scans retrieved from the collection of the Radiology Center of the School of Dentistry - São Leopoldo Mandic. Methods: A total of 181 images were analyzed by means of multiplanar reconstructions. Results were subjected to biostatistics. Results: The prevalence of pulp stones was 55%. Prevalence was highest in the 31-40 year age group (89.7%) and in the group of teeth that had been restored (61%). Teeth #16 was the most affected, at a prevalence of 12.8 %, followed by #17 (10.3%). Conclusion: The prevalence of patients with pulp stones was 55%. Pulp stones were not associated with aging. Most teeth with pulp stones were maxillary permanent molars, and tooth restoration may be the cause of stone formation.
Keywords: Cone-beam computed tomography; Dental pulp calcification; Dental pulp diseases